Slow-paced breathing reduces anxiety and enhances midfrontal alpha asymmetry, buffering responses to aversive visual stimuli - Iwabe, Tatsuya; Miyakawa, Akari; Kodama, Soshi; Yoshida, Susumu (Frontiers in Human Neuroscience, 2025)
IntroductionSlow-paced breathing (SB) reduces anxiety, but its effects on frontal alpha asymmetry (also termed relative left frontal activity, rLFA) and the persistence of these effects after aversive stimuli remain unclear. This study investigated whether SB reduces state anxiety and enhances rLFA, and whether these effects persist immediately after exposure to aversive images from the International Affective Picture System (IAPS) following the breathing task.MethodsSeventeen healthy participants (7 females) completed sessions of SB (4 s inhalation, 6 s exhalation) and resting breathing (RB). Electroencephalography (EEG), heart rate variability (HRV), respiratory parameters, and State-Trait Anxiety Inventory-State (STAI-S) scores were measured at baseline (pre-task), post-task, and post-stimuli. HRV was evaluated by the root mean square of successive differences (RMSSD) and the low-frequency/high-frequency ratio (LF/HF ratio). Respiratory measurements included respiratory rate, coefficient of variation of respiratory intervals (CVRR), and end-tidal CO2 (ETCO2). rLFA, measured by alpha wave activity, was calculated at midfrontal (F4-F3) and lateral frontal (F8-F7) EEG sites.ResultsSTAI-S scores in SB condition were significantly lower than in RB condition, both post-task (p < 0.001, Cohen’s d = −1.46) and post-stimuli (p < 0.001, Cohen’s d = −1.25). Midfrontal rLFA (F4-F3) also significantly increased with SB post-task (p < 0.01, Cohen’s d = 1.03) and post-stimuli (p < 0.05, Cohen’s d = 0.84), whereas lateral frontal rLFA (F8-F7) showed no significant changes. A significant interaction between intervention and time was observed for RMSSD (p < 0.01, η2G = 0.18). Post-task RMSSD was significantly lower in SB condition compared to RB condition (p < 0.001), but this difference was absent post-stimuli.DiscussionThese findings suggest that SB effectively reduces state anxiety while enhancing rLFA, with these effects persisting after exposure to visual stressors. The anxiety-buffering effect of SB may be mediated by enhanced rLFA in the midfrontal region, reflecting improved prefrontal regulatory control over emotion. This indicates that SB could be a practical intervention to enhance neurophysiological resilience against acute stress.